Reducing the Number of Training Cases in Genetic Programming - Zoppi, Giacomo (2022)
Zoppi, G., Vanneschi, L., & Giacobini, M. (2022). Reducing the Number of Training Cases in Genetic Programming. In 2022 IEEE Congress on Evolutionary Computation (CEC) (pp. 1-8). IEEE. https://doi.org/10.1109/CEC55065.2022.9870327